The mediating effect of work category on the relationship between professional competencies` and decision making among public relations in government- linked companies - Khairul Nizam Samsudin,; Zulhamri Abdullah,; Mohd Nizam Osman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Organisational success can only be materialized when each stakeholder mutually agrees to benefit each other, thus making the organisation effective. And here is the main role of public relations (PR), were to be the middle person between each stakeholder, by performing their works through the competencies they mastered, to ensure that the decisions made will be valuable to organisation and stakeholders. The objective of this study is to examine the mediating effect of work category on the relationship between professional competencies and decision making among PR practitioners in government-linked companies (GLCs). A survey questionnaire was gathered from 157 PR practitioners and data were analysed through SEM PLS. Results indicated that the dimension of work category did influence the relationship between professional competency and decision making. In essence, the decision-making process of a PR practitioner working in Malaysia's GLCs can be enhanced or improved based on the level of professional competencies. The implication of these findings supported the role of the PR department as part of the important sub-system in organisation and competencies acquired by PR practitioners is the resource that able to maintain the survival of an organisation. In the nutshell, a large-scale study should be undertaken, which incorporate a large group of participants in the future to accommodate the responses from a wide population to increase the accuracy of results.